1998
DOI: 10.1093/hmg/7.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the canilicular multispecific organic anion transporter (cMOAT) gene, a novel ABC transporter, in patients with hyperbilirubinemia II/Dubin-Johnson syndrome

Abstract: Members of the ATP-binding cassette (ABC) transporter superfamily are mutated to cause diseases that include cystic fibrosis, hyperinsulinemia, adrenoleukodystrophy, Stargardt disease and multidrug resistance. We recently isolated a novel human member of ABC transporter superfamily as the candidate transporter for the glucuronide and glutathione-conjugated antitumor agents, and found it highly homologous to the rat cmoat gene. consistent with recent findings of defects in the homologous cmoat gene in two rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
125
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(131 citation statements)
references
References 22 publications
4
125
0
2
Order By: Relevance
“…Two aliquots of at least 0.7 ml of plasma each were removed, placed in screw-cap polypropylene tubes and immediately stored at À20 1C or below until the analysis. Blood samples were collected before and at 0.5, 1, 1.5, 2, 3, 4,6,8,12,16,24,36,48,60 and 72 h following each dose. The plasma concentrations of olmesartan were determined by a validated method of high-performance liquid chromatography with fluorescence detection.…”
Section: Sample Treatments and Pharmacokinetic Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Two aliquots of at least 0.7 ml of plasma each were removed, placed in screw-cap polypropylene tubes and immediately stored at À20 1C or below until the analysis. Blood samples were collected before and at 0.5, 1, 1.5, 2, 3, 4,6,8,12,16,24,36,48,60 and 72 h following each dose. The plasma concentrations of olmesartan were determined by a validated method of high-performance liquid chromatography with fluorescence detection.…”
Section: Sample Treatments and Pharmacokinetic Data Analysismentioning
confidence: 99%
“…11 With regard to ABCC2, several mutations and deletions have been identified in patients with Dubin-Johnson syndrome, an autosomal recessive disorder, each of which impairs either the expression or function of MRP2 protein. [12][13][14] Beside mutations in Dubin-Johnson syndrome, the extensive genetic variation identified so far may have a potential effect on drug disposition. 15,16 In fact, the T allele of À24C4T has been associated with lower mRNA levels in normal renal tissues, leading to reduced transporter activity.…”
Section: Introductionmentioning
confidence: 99%
“…A deletion of residue F508 in NBD1 is the most common (Riordan et al 1989). The Dubin-Johnson syndrome is conferred by mutations in the ABCC2 gene, leading to a deficiency in canalicular multispecific organic anion transport and bilirubin accumulation in liver (Wada et al 1998). Long chain fatty acids are transported by ABCD1, and Adrenoleukodystrophy (ADL) is a genetically inherited disease, caused by mutations in the ABCD1 gene (Mosser et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…2,3,10,11,22 The occurrence of distinct MRP isoforms in hepatocytes has been initially shown by amplification and sequencing of novel complementary DNA (cDNA) fragments, by immunoblotting, and by immunofluorescence microscopy. 5 The canalicular MRP isoform deficient in Dubin-Johnson syndrome was identified as MRP2, 21,23,24 however, the molecular identity of the MRP isoform(s) localized to the lateral or basolateral hepatocyte membrane 5,23,25 remained uncertain. RNase protection assays indicated that the liver expresses MRP2, MRP3, MRP5, and MRP6, but hardly MRP1.…”
mentioning
confidence: 99%